ANALISIS PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Pada CV. Fan Jaya Logam Kaliwungu) - Ameliawati, Rizqi; Nugraheni, Rini (Diponegoro Journal of Management, 2015)
This research background by the complaints from managers and employees CV. Fan Jaya Logam. In the perceived grievances, there are problems associated with corporate leaders, working conditions, compensation and employee performance. By looking at existing problems, this research is directed to investigate and analyze the influence of leadership, work environment, and motivation on employee performance CV. Fan Jaya Logam.In this study, researchers used census method, with a total respondents of 80 person. To facilitate troubleshooting, research was conducted by using multiple linear regression analysis with SPSS 17.0.The results of this study are : leadership has a positive influence on the performance of the employee, the work environment has a positive effect on employee performance, compensation has a positive influence on employee performance. Suggestions for further research, you should consider other variables that are still closely related to the variables in this study.